The relationship of placental histology to pregnancy and neonatal characteristics in preterm infants - (:unkn) unknown (My University, 2008)
Objective: The microscopic and macroscopic features of placenta can contribute to the clinical understanding of premature delivery. The aim of our study was to relate the histopathological findings in the placentas of premature infants to pregnancy and explore its relation to neonatal morbidity. Materials and Methods: Placentas of 86 singleton preterm infants were examined and the association between placental pathology and the initiator of the preterm delivery such as preterm labor (PTL), preterm premature rupture of membranes (P-PROM) and pregnancy induced hypertension (PIH) were evaluated. The findings associated with acute placental inflammation or placental evidence of PIH were correlated to the initiators of preterm delivery and the clinical findings of the neonates. Results: The initiator of preterm delivery was PTL in 45%, P-PROM in 20% and PIH in 21% of the infants. Twenty percent of placentas had one or more findings associated with acute inflammation, 43% had findings associated with PIH, 23% had no identifiable pathology and 14% had other findings (intervillous thrombus, villous edema, etc.). Among mothers with placental evidence of acute inflammation, 56% had P-PROM, 38% had PTL and 6% had PIH. The mothers who had histological chorioamnionitis delivered at a younger gestational age than the mothers who had placental evidence of PIH (29 and 32 weeks, respectively; p=0.001). Histological chorioamnionitis was found to be more frequent in the placentas of infants with bronchopulmonary dysplasia (p=0.001). Discussion: This preliminary study revealed that the placental pathological findings appear to be correlated to the initiator of preterm delivery. Examination of the preterm delivery placentas gains importance in determining the etiology of preterm delivery and morbidity in infants.
Keywords: Histological chorioamnionitis; Neonatal morbidity; Placenta; Prematurity